Continuous-Variable Pairwise Entanglement Based on Optoelectromechanical System - Cai, Qizhi; Liao, Jinkun; Zhou, Qiang (Quantum engineering, 2023)
We show how to generate stationary continuous-variable pairwise entanglement between microwave modes in a hybrid optoelectromechanical system, which consists of a single Fabry–Pérot cavity, a parallel-plate capacitor with a moving element as the mechanical resonator, and several pairs of microwave cavities. The optical mode and mechanical resonator are coupled via radiation pressure; meanwhile, several pairs of the microwave mode and mechanical resonator are capacitively coupled. Under an experimentally reachable parameter regime, we show the influence of different key parameters on pairwise entanglement and find that it is also robust against temperature. Our model and results are expected to provide a new perspective on quantum networks with increasingly large scales, quantum internet with multiple local users, and multiport microwave quantum illumination radar.